Prevalensi dan Kelimpahan Ektoparasit pada Ikan Belanak (Mugil Cephalus) Hasil Tangkapan di Muara Sungai Serayu Adipala Cilacap - Pajrulloh, Ade Rizki; Rokhmani, Rokhmani; Riwidiharso, Edy (Fakultas Biologi Universitas Jenderal Soedirman, 2022)
Belanak (Mugil cephalus) is a fish that can adapt to a wide salinity 17-30% and its distribution in tropical to subtropical areas, so that mullet can be found in rivers to river mouths, one of which is found in the Serayu River Estuary, Adipala Cilacap. Fish diseases can be caused by parasites, one of which is ectoparasites. Ectoparasites are organisms that benefit from infesting the body surface of fish. This study aims to determine the prevalence of mullet infested with ectoparasites and to determine the abundance of ectoparasites in mullet (Mugil cephalus) in the Serayu Adipala River, Cilacap. The research method used is survey method with purposive random sampling technique. The variables observed were the prevalence and abundance of ectoparasites. The parameters observed were the type and number of ectoparasites found in mullet. The results showed that the prevalence of ectoparasites in mullet, which was 31±13.216%, was included in the general infestation category. The types of ectoparasites found were Dactylogyrus sp. and Apiosoma sp. The abundance of ectoparasites found in mullet is Dactylogyrus sp. of 0.25±0.14 ind/head and Apiosoma sp. of 0.36± 0.14 ind/head. Both results included in the category of very rare infestations and the highest ectoparasites found in the organs of the mullet fish were found in the gills, namely Dactylogyrus sp. as many as 25 individuals.